The Influence Of Concept Map And Mind Mapping On Students' Concept Understanding And Mathematical Reasoning Ability - Azizah, Nurlia; Sitorus, Masganti; Reflina (Yana Research, 2023)
This study aims to find out whether there is an influence on the ability to understand concepts and mathematical reasoning of students who are taught with Concept Maps and Mind Mapping in class VIII MTs Daar al-Uluum Asahan Modern Islamic Boarding School in the 2021-2022 Academic Year Range. This research is a quantitative research with a quasi-experimental research type. The population is all class VIII students of MTs Modern Daar al-Uluum Asahan Islamic Boarding School for the 2021-2022 Academic Year Range, consisting of 2 classes and a total of 60 students, who were also sampled in this study. The test instrument used to determine students' ability to understand concepts and mathematical reasoning is in the form of a description. Data analysis was carried out by analysis of variance (ANAVA). The results of these findings showed: 1). The ability to understand concepts of students who were taught using the Concept Map was better than students who were taught with Mind Mapping in the material of Number Patterns in class VIII; 2). The mathematical reasoning ability of students who were taught by using Concept Map was no better than students who were taught by Mind Mapping on Number Pattern material in grade VIII; 3). The ability to understand concepts and mathematical reasoning of students who were taught by using the Concept Map was better than students who were taught by Mind Mapping in the material of Number Patterns in class VIII; 4). There is a significant interaction between the learning methods used and the ability to understand concepts and students' mathematical reasoning in the matter of number patterns. The conclusion in this study explains that students' conceptual comprehension and mathematical reasoning abilities are more appropriate to be taught with concept maps than mind maps.